(untitled) (Verba Vitae Unwira, 2020)
Traditional marriage of Bataknese is a cultural obligation and a social norm. For Batak community, wedding preparations with a number of stagesis mandatory in order to preserveculture. The aims of this study are three folds: to identify and explain communication activities in ‘Pariban’a tradition of Toba Batak tribe;to analyze the meaning of Pariban; and to explain the values ??contained inPariban. This is a qualitative studythat applies ethnographic method of communication. This method was chosen because it is applicable in determining the communication activities and values ??in Pariban.The results uncover that marriage with Pariban is an easier marriage, especially in determining the dowry or bride price. However, the practice of Paribanthese days tends to be ignored. The stages in marriage practiced in Toba Batak tribe includes pre-marriage, marhori-horiDinding, marhusip, marhatasinamot, martumpol, martanggo raja and marria raja, marsibuha-buhai, religious ceremonies, and customary celebration. All these stages contain communication events, communication situations and contexts, and communication actions as three elements in communication ethnography.